2009
DOI: 10.1103/physrevb.80.180507
|View full text |Cite
|
Sign up to set email alerts
|

Local density of states and superconducting gap in the iron chalcogenide superconductorFe1+δSe1xTe

Abstract: We report on the investigation of the quasiparticle local density of states and superconducting gap in the iron chalcogenide superconductor Fe 1+␦ Se 1−x Te x ͑T c ϳ 14 K͒. The surface of a cleaved crystal revealed an atomic square lattice, superimposed on the inhomogeneous background, with a lattice constant of ϳ3.8 Å without any reconstruction. Tunneling spectra measured at 4.2 K exhibit the superconducting gap, which completely disappears at 18 K, with a magnitude of ϳ2.3 meV, corresponding to 2⌬ / k B T c … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
70
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 30 publications
(39 reference statements)
16
70
1
Order By: Relevance
“…Figure 1(c) and (d) show the atomically-resolved STM images with opposite-polarity bias on the same location of a cleaved FeTe surface. They are similar to previous STM studies of Fe-chalcogenides [16][17][18] , where no reconstruction is observed. The lattice constant estimated from Fourier transform of the image is ∼ 3.8Å, in good agreement with that obtained from the bulk 14 .…”
supporting
confidence: 80%
See 3 more Smart Citations
“…Figure 1(c) and (d) show the atomically-resolved STM images with opposite-polarity bias on the same location of a cleaved FeTe surface. They are similar to previous STM studies of Fe-chalcogenides [16][17][18] , where no reconstruction is observed. The lattice constant estimated from Fourier transform of the image is ∼ 3.8Å, in good agreement with that obtained from the bulk 14 .…”
supporting
confidence: 80%
“…Note that similar images were obtained in previous STM studies on the doped compounds 17,18 . Both filled-state or empty-state images show very similar contrast of two groups of atoms.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…In the '11' system, the multi-gap feature was recently found to form 2Δ L / k B T c ≈ 4 -8.3 and 2Δ S / k B T c ≈ 0.8 -4 in optics, 49 μSR, 50 STS, 51 and specific heat studies. 52 It is thus important to note that the 2Δ L enhancement factor, corresponding to ~ 1 -2.4 times of 2Δ BCS , is generally larger than that of LiFeAs, indicating that the strong-coupling effect in the 2Δ L is more pronounced than the '111' case.…”
Section: E Enhancement Of the Pauli-limiting Fieldmentioning
confidence: 99%